1999
DOI: 10.1128/jb.181.14.4198-4204.1999
|View full text |Cite
|
Sign up to set email alerts
|

The Yersinia enterocolitica pYV Virulence Plasmid Contains Multiple Intrinsic DNA Bends Which Melt at 37°C

Abstract: Temperature has a pleiotropic effect on Yersinia enterocolitica gene expression. Temperature-dependent phenotypes include the switching between two type III protein secretion systems, flagellum biosynthesis (≤30°C) and virulence plasmid-encoded Yop secretion (37°C). The mechanism by which temperature exerts this change in genetic programming is unclear; however, altered gene expression by temperature-dependent changes in DNA topology has been implicated. Here, we present evidence that the Y. enterocolitica vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 32 publications
4
37
0
Order By: Relevance
“…It has been shown that a transition from 25∞C to 37∞C induces structural alterations, e.g. relaxation and melting of DNA bends, and these changes can reduce the interaction of H-NS, which no longer prevents the formation of a productive transcriptional complex and allows the expression of virulence genes at higher temperatures (Falconi et al, 1998;Rohde et al, 1999;Madrid et al, 2002;Prosseda et al, 2004). The inv and rovA promoters both contain long and flexible AT-rich sequences, and temperature-dependent changes in the DNA flexibility might trigger a structural transition that modulates the accessibility to H-NS in reverse to the usual situation in other virulence systems.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a transition from 25∞C to 37∞C induces structural alterations, e.g. relaxation and melting of DNA bends, and these changes can reduce the interaction of H-NS, which no longer prevents the formation of a productive transcriptional complex and allows the expression of virulence genes at higher temperatures (Falconi et al, 1998;Rohde et al, 1999;Madrid et al, 2002;Prosseda et al, 2004). The inv and rovA promoters both contain long and flexible AT-rich sequences, and temperature-dependent changes in the DNA flexibility might trigger a structural transition that modulates the accessibility to H-NS in reverse to the usual situation in other virulence systems.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to yspP, yopH appears to have similar expression levels in both spent DMEM and during HeLa cell infection, which would appear to contradict the results shown in Figure 2. It should be noted, however, that expression of the Ysc T3SS has been shown to be induced at 37°C, due to changes in the secondary structure of the virulence plasmid (Rohde et al 1999) and the ribosome-binding site of the transcriptional activator LcrF (Bohme et al 2012) at that temperature.…”
Section: Qrt-pcr Quantification Of Ysa Expression In Vitromentioning
confidence: 99%
“…DNA with a bent trajectory in its helical axis that is induced solely by innate nucleotide sequences, such as phased homopolymeric adenine:thymine tracts (AT‐tracts), is called intrinsically curved DNA (Ohyama, 2001). We showed previously that multiple intrinsically curved DNAs are present in the virulence plasmids of Yersinia enterocolitica , enteropathogenic E. coli and enterohaemorrhagic E. coli (Rohde et al ., 1999).…”
Section: Introductionmentioning
confidence: 99%